Co-Magneli phases electrocatalysts for hydrogen/oxygen evolution - Perica Paunovic, Orce Popovski, Emilija Fidancevska, Bogdan Ranguelov, Dafinka Stoevska Gogovska, Aleksandar T. Dimitrov, Svetomir Hadzi Jordanov (Elsevier, 2010)
The subject of this work is the use of non-stoichiometric titanium oxides e Magneli phases as support material of Co-based electrocatalysts aimed for hydrogen/oxygen evolution reaction. Commercial micro-scaled Ebonex (Altraverda, UK) was mechanically treated for 4, 8, 12, 16 and 20 h and further Co metallic phase was grafted by sol-gel method. Morphology of Co/Ebonex electrocatalysts was observed by means of TEM and SEM microscopy, while electrochemical behavior by means of cyclic voltammetry and steadystate galvanostatic method. As the duration of mechanical treatment increases, the size of Magneli phases decreases, and consequently catalytic activity of the corresponding electrocatalysts increases. Structural characteristics of the electrocatalysts deposited on Ebonex treated for 16 and 20 h are very similar. Also, these electrocatalysts show similar electrocatalytic activity for both hydrogen and oxygen evolution reaction. So, optimal duration of mechanical treatment of Magneli phases is in the range of 16e20 h. Catalytic activity for hydrogen evolution of the studied electrocatalysts is inferior related to the corresponding catalysts deposited on carbonaceous support materials such as activated multiwalled carbon nanotubes or Vulcan XC-72 þ TiO2 (anatase). This inferiority is due to lower real surface area of the Magneli phases. Catalytic behavior for oxygen evolution achieves its maximal value even at the catalyst deposited on Ebonex treated for 12 h and it is very promising related to the similar electrocatalytic system such as CoPt/Ebonex.